And What Were You Like in Hades? Eur. HF 1410–1417 - Kostyleva, Tatiana (Hyperboreus, 2017)
The much-maligned lines Eur. HF 1410–1417 are treated in this article as a psychologically veritable conclusion – should we not wish to follow N. Wecklein and bluntly round off at 1404 – of the Amphitryon–Heracles–Theseus scene in which they are most at home where the tradition has them, at the very end, and not, as G. Bond would attempt to prove, immediately after 1253. Along the way to 1417 certain minor critical comments are offered.